UPAYA PENINGKATAN KINERJA PELAYANAN KARYAWAN PADA AKADEMI PARIWISATA INDRAPHRASTA YOGYAKARTA - Teniwut, Roberto Mario Kabi (Jurnal MS, 2014)
This research was conducted to see the quality of service the employee division ofÂ academic, administrative, financial, library and computer labs at Indraphrasta Academic Tourism of Yogyakarta. Source of data used are primary and secondary data with a four-month study period. While the methods used are surveys andÂ observations with analysis tools both of SWOT analysis and description. TheÂ results of the first, the general implementation of education and training for theÂ employees of each division in the Academic Indraphrasta Tourism YogyakartaÂ still needs to be improved and developed. Second, the importance of continuingÂ education for employees who have not reached the required standards and theÂ need for recruitment of prospective employees who have the competence, thusÂ meeting the needs of qualified human resources. Third, the need for the activitiesÂ carried out by the Indraphrasta Academic Tourism of Yogyakarta involving all existing employees. Recomendation that can be given is to transfer power to the personnel who have the ability and experience. Secondly, before the candidate recruitment process should be set in advance the standards of the qualification of human resources required. Third, the need for out bound activities to employees. Fourth, the importance of the leadership role that always keep the employees keep working optimally in accordance with their competence, for example, share a vision. Fifth, the need for periodic meetings with the leaders of two weeks. Sixth, do renewal office equipment. Seventh, the need for promotion and marketing activities through cooperative relationships with government agencies or private. Recently the need for education and ongoing training for employees in order to improve performance.